Nabycie służebności przesyłu w drodze zasiedzenia - Sokołowski, Łukasz (Europejskie Stowarzyszenie Studentów Prawa ELSA Poznań, 2012)
The paper is an attempt to determine the admissibility of acquisition of a transmission easement by virtue of usucaption. It also contains the review and assessment of the main issues, doubts and discrepancies which are present in the doctrine and jurisprudence. The survey also deals with deliberations concerning the possibilities of usucaption of particular ways of using the facilities as referred in the article 49 of The Civil Code prior to the amendments of The Civil Code of 20 May 2008 that introduced a new legal institution of a utility of transmission easement.
Usucaption of a transmission easement
Keywords: transmission easement; acquisition of a transmission easement; transmission facilities; usucaption; entrepreneur; easement appurtenant; real servitude; limited right in property